Field and Service Robotics Results of the 11th International Conference - Hutter, Marco; Siegwart, Roland (Springer Proceedings in Advanced Robotics, 2018)
This book contains the proceedings of the 11th FSR (Field and Service Robotics), which is the leading single-track conference on applications of robotics in challenging environments. This conference was held in Zurich, Switzerland from 12-15 September 2017. The book contains 45 full-length, peer-reviewed papers organized into a variety of topics: Control, Computer Vision, Inspection, Machine Learning, Mapping, Navigation and Planning, and Systems and Tools. The goal of the book and the conference is to report and encourage the development and experimental evaluation of field and service robots, and to generate a vibrant exchange and discussion in the community.  Field robots are non-factory robots, typically mobile, that operate in complex and dynamic environments:  on the ground (Earth or other planets), under the ground, underwater, in the air or in space.  Service robots are those that work closely with humans to help them with their lives.  The first FSR was held in Canberra, Australia, in 1997. Since that first meeting, FSR has been held roughly every two years, cycling through Asia, Americas, and Europe.